Persistent Neuromuscular and Corticomotor Quadriceps Asymmetry After Anterior Cruciate Ligament Reconstruction - Kuenze, Christopher M. (J Athl Train, 2015)
CONTEXT: Return to activity in the presence of quadriceps dysfunction may predispose individuals with anterior cruciate ligament reconstruction (ACLR) to long-term joint degeneration. Asymmetry may manifest during movement and result in altered knee-joint–loading patterns; however, the underlying neurophysiologic mechanisms remain unclear. OBJECTIVE: To compare limb symmetry of quadriceps neuromuscular function between participants with ACLR and participants serving as healthy controls. DESIGN: Descriptive laboratory study. SETTING: Research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 22 individuals with ACLR (12 men, 10 women) and 24 individuals serving as healthy controls (12 men, 12 women). MAIN OUTCOME MEASURE(S): Normalized knee-extension maximal voluntary isometric contraction (MVIC) torque (Nm/kg), quadriceps central activation ratio (CAR) (%), quadriceps motor-neuron–pool excitability (Hoffmann reflex to motor wave ratio), and quadriceps active motor threshold (AMT) (% 2.0 T) were measured bilaterally and used to calculate limb symmetry indices for comparison between groups. We used analyses of variance to compare quadriceps Hoffmann reflex to motor wave ratio, normalized knee-extension MVIC torque, quadriceps CAR, and quadriceps AMT between groups and limbs. RESULTS: The ACLR group exhibited greater asymmetry in knee-extension MVIC torque (ACLR group = 0.85 ± 0.21, healthy group = 0.97 ± 0.14; t(44) = 2.26, P = .03), quadriceps CAR (ACLR group = 0.94 ± 0.11, healthy group = 1.00 ± 0.08; t(44) = 2.22, P = .04), and quadriceps AMT (ACLR group = 1.13 ± 0.18, healthy group = 1.02 ± 0.11; t(34) = −2.46, P = .04) than the healthy control group. CONCLUSIONS: Asymmetries in measures of quadriceps function and cortical excitability were present in patients with ACLR. Asymmetry in quadriceps strength, activation, and cortical excitability persisted in individuals with ACLR beyond return to recreational activity. Measuring the magnitude of asymmetry after ACLR represents an important step in understanding long-term reductions in self-reported function and increased rate of subsequent joint injury in otherwise healthy, active individuals after ACLR.